Successful Treatment of SCD-Related Priapism With Crizanlizumab: A Case Series - Modupe Idowu MD; Roberto L. Garcia MD; Oluwatosin B. Sule FNP-C (SAGE Publishing, 2023)
Priapism, an unwanted, painful, prolonged erection that is unrelated to sexual stimulation, is a common complication of sickle cell disease (SCD). Priapic events in SCD are stuttering, meaning they occur repeatedly with intervening periods of detumescence. Without health care intervention, repeated episodes can lead to erectile dysfunction. There are limited treatment options for SCD-related priapism and no approved targeted therapies. Crizanlizumab is a monoclonal antibody that binds to P-selectin and is used to reduce the frequency of vaso-occlusive crises in patients with SCD. Here, we report the cases of 3 patients with SCD-related priapism who were treated with crizanlizumab. All patients were African American men who experienced numerous priapic episodes that interfered with their daily lives. Upon treatment with crizanlizumab, priapic events were reduced in all 3 patients. These successful cases suggest a potential role for crizanlizumab in the prevention of SCD-related priapism.